Modulation of microbiome diversity and cytokine expression is influenced in a sex-dependent manner during aging - Webster, Sarah E.; Vos, Duncan; Rothstein, Thomas L.; Holodick, Nichol E. (Frontiers in Microbiomes, 2022)
The microbiome and immune system have a unique interplay, which influences homeostasis within the organism. Both the microbiome and immune system play important roles in health and diseases of the aged including development of cancer, autoimmune disorders, and susceptibility to infection. Various groups have demonstrated divergent changes in the gut microbiota during aging, yet the compounding factor of biological sex within the context of aging remains incompletely understood, and little is known about the effect of housing location in the composition of gut microbiota in the context of both sex and age. To better understand the roles of sex, aging, and location in influencing the gut microbiome, we obtained normal healthy BALB/cByJ mice from a single source and aged male and female mice in two different geographical locations. The 16S rRNA was analyzed from fecal samples of these mice and cytokine levels were measured from serum.16S rRNA microbiome analysis indicated that both age and sex play a role in microbiome composition, whereas location plays a lesser role in the diversity present. Interestingly, microbiome changes occurred with alterations in serum expression of several different cytokines including IL-10 and IL-6, which were also both differentially regulated in context to sex and aging. We found both IL-10 and IL-6 play a role in the constitutive expression of pSTAT-3 in CD5+ B-1 cells, which are known to regulate the microbiome. Additionally, significant correlations were found between cytokine expression and significantly abundant microbes. Based on these results, we conclude aging mice undergo sex-associated alterations in the gut microbiome and have a distinct cytokine profile. Further, there is significant interplay between B-1 cells and the microbiome which is influenced by aging in a sex-dependent manner. Together, these results illustrate the complex interrelationship among sex, aging, immunity, housing location, and the gut microbiome.